Lesions in nucleus basalis magnocellularis and medial septal area of rats produce qualitatively similar memory impairments - Hepler, DJ (J Neurosci, 1985)
The functional contribution of nucleus basalis magnocellularis (NBM) and the medial septal area (MSA) to memory was evaluated in two different spatial discriminations. Preoperatively, rats were trained to a criterion level of performance in a simultaneous left/right discrimination on the stem of a T-maze (a trial-independent memory) and a discrete-trial, rewarded alternation discrimination on the arms of the T-maze (a trial-dependent memory). Bilateral lesions were made by injecting ibotenic acid (IBO) into the NBM, MSA, both NBM and MSA, or dorsal globus pallidus (DGP), and by radiofrequency current (RF) in the NBM and MSA. Control rats received operations in which either no current was passed or no neurotoxin was injected. Lesions in the NBM, MSA, or both the NBM and MSA produced a similar pattern of behavioral changes relative to the performance of controls; postoperative reacquisition of the arm discrimination was initially impaired but showed recovery to normal levels, whereas postoperative reacquisition and reversal of the stem discrimination was not impaired (except following the combined NBM and MSA lesion). Lesions of the DGP had no effect on choice accuracy in any discrimination. When the discrimination on the arms was made more difficult by increasing the delay interval during which the information had to be remembered, rats with combined NBM and MSA lesions were again impaired relative to controls and showed no signs of recovery of function. These results provide information about the behavioral functions of the basal forebrain cholinergic system and suggest that pathological changes in certain components of this system can cause disorders of memory.